Analisis Perbandingan Metode Produksi Film Dokumenter: Pendekatan Vertikal Vs. Horizontal - Rusman Latief; Dian Dian; Nurohmat Nurohmat (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study aims to analyze the general process of documentary film production, including independent documentaries, television documentaries, and documentaries produced for cinemas. In its production, documentary films typically involve professionals with specialized expertise, such as scriptwriters, directors, cinematographers, sound designers, and editors. However, with technological advancements, documentary film production can now be carried out with fewer crew members, even by a single individual. Therefore, there are two production approaches: the vertical method and the horizontal method. The vertical method refers to production conducted independently by one or a few individuals, while the horizontal method involves a larger production team. This study employs a qualitative method with a document study approach, collecting information from various sources, including books, scientific journals, and relevant online media. The research findings indicate that documentary film production approaches can be categorized into vertical and horizontal methods. The choice of production method is influenced by various factors, such as the historical development of documentary films, the education level and experience of the crew, and the production concept.